Direct Amplification, Sequencing and Profiling of Chlamydia trachomatis Strains in Single and Mixed Infection Clinical Samples - Joseph, Sandeep J. (Public Library of Science, 2014)
Sequencing bacterial genomes from DNA isolated directly from clinical samples offers the promise of rapid and precise acquisition of informative genetic information. In the case of Chlamydia trachomatis, direct sequencing is particularly desirable because it obviates the requirement for culture in mammalian cells, saving time, cost and the possibility of missing low abundance strains. In this proof of concept study, we developed methodology that would allow genome-scale direct sequencing, using a multiplexed microdroplet PCR enrichment technology to amplify a 100 kb region of the C. trachomatis genome with 500 1.1–1.3 kb overlapping amplicons (5-fold amplicon redundancy). We integrated comparative genomic data into a pipeline to preferentially select conserved sites for amplicon design. The 100 kb target region could be amplified from clinical samples, including remnants from diagnostics tests, originating from the cervix, urethra and urine, For rapid analysis of these data, we developed a framework for whole-genome based genotyping called binstrain. We used binstrain to estimate the proportion of SNPs originating from 14 C. trachomatis reference serotype genomes in each sample. Direct DNA sequencing methods such as the one described here may have an important role in understanding the biology of C. trachomatis mixed infections and the natural genetic variation of the species within clinically relevant ecological niches.